Labisia Pumila Extract Down-Regulates Hydroxysteroid (11-beta) Dehydrogenase 1 Expression and Corticosterone Levels in Ovariectomized Rats - M. M., Yusoff; Fazliana, Mansor; Gu, Harvest F.; Östenson, Claes-Göran; Wan Mohamud, Wan Nazaimoon (Springer Japan, 2012)
We evaluated the effects of a standardized Labisia pumila var. alata (LPva) extract on body weight change, hydroxysteroid (11-beta) dehydrogenase 1 (HSD1 1B1) expressions and corticosterone (CORT) level in ovariectomized (OVX) rats. The decoction of LPva has been used for generations among Malay women in Malaysia to maintain a healthy reproductive system.Thirty-six Sprague–Dawley OVX rats were treated orally with LPva extract (10, 20 or 50 mg/kg/day) or estrogen replacement (ERT) for 30 days. Sham operated rats were used as controls. Compared to untreated OVX rats, LPva-treated rats showed less weight gain and had significantly down-regulated HSD11B1 mRNA in liver tissues. HSD11B1 mRNA in adipose tissues increased by 55% (p\0.05) in OVX rats but normalized in rats treated with LPva. Similarly, there was significant down-regulation (p\0.05) of protein levels of HSD11B1 in both liver and adipose tissue of LPva and ERT groups, and CORT levels were significantly reduced in both groups of rats. This is the first study ever conducted to evaluate the beneficial effects of LPva in relation to weight gain caused by estrogen insufficiency. Results implied that the bioactive components in LPva extract affect not only HSD11B1 expressions in both adipose and liver tissues but also decrease circulating CORT. The extract should be explored for its potential use as a natural remedy for weight management.